Emergency Transcatheter Arterial Embolization for Acute Mediastinal Hemorrhage - Ling, Gonghao; Zhou, Jun; Ding, Xun; Long, Qingyun (The Thoracic and Cardiovascular Surgeon, 2021)
Purpose The aim of this study was to investigate the application value of transcatheter arterial embolization (TAE) for mediastinal hemorrhage.Materials and Methods The study retrospectively analyzed the status of TAE treatment in 13 patients with mediastinal hemorrhage.Results Aortic angiography and bleeding artery angiography showed that the bleeding in 13 mediastinal hemorrhage patients, respectively, originated from intercostal artery, esophageal artery, or bronchial artery. All patients were embolized with gelatin sponge and (or) polyvinyl alcohol particles. Chest computed tomography scan found that all 13 patients showed reduced range of mediastinal hematoma after TAE.Conclusion TAE has the advantages of reduced trauma, rapid and direct hemostasis, and solid therapeutic effects in the treatment of mediastinal hemorrhage.
Keywords: imaging; mediastinal hemorrhage; transcatheter arterial embolization; artery/arteries